Josephson effect in a weak link between borocarbides - Kolesnichenko, Yu.A.; Shevchenko, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
A stationary Josephson effect is analyzed theoretically for a weak link between borocarbide superconductors. It is shown that different models of the order parameter result in qualitatively different current-phase relations.